Menilik Efektivitas Pelaksanaan E-government Pemerintah Daerah - Ashar Prawitno; Andi Irpan Badawi; Aiman Sabar Rezeky (SOCIETAS, 2022)
The implementation of information technology-based governance (e-government) is increasingly being encouraged and developed by local governments, but there are always problems that occur. The same thing happened in the implementation of e-government in Gowa Regency. The purpose of this study was to determine the implementation of e-government and the factors that influence the implementation of e-government in Gowa Regency. This research is a qualitative research with data collection techniques through interviews, observation, documentation, and literature study. The results of the study indicate that the implementation of e-government in Gowa Regency has not been effective enough, although in terms of input there has been a legal umbrella in the form of Gowa Regent Regulation Number 37 of 2017 and in terms of production there are facilities for making websites and applications at the Office of Communication, Information, Statistics, and Gowa Regency coding, but in terms of output, it turns out that most of the Regional Government Work Units (SKPD) in Gowa Regency do not have websites or supporting applications in the implementation of e-government. So far, only 13 of the 36 SKPD have websites. The factors that influence the implementation of e-government in Gowa Regency, namely the lack of coordination between SKPD in Gowa Regency, the geographical condition of Gowa Regency which is mostly highlands resulting in uneven internet network accessibility, lack of human resources (SDM) capabilities, facilities and infrastructure have not been developed. qualified, and the availability of the budget is not sufficient.